Limbaga (Proverbs) Simalungun as a Source of Forming Character Education - Asriaty R. Purba; Herlina Herlina; Jamorlan Siahaan (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This research is entitled Limbaga (Proverbs) Simalungun as a Source of Formation of Character Education. Character education is a human activity to establish peace-loving and prosperous personalities in order to build their own personal character and people around them. Character education is closely related to moral education which aims to shape and practice one's ability to perfect him in a better direction. Character education has been applied since childhood. Character education can be done in their family, school and community. The purpose of this study is to describe the character values contained in limbaga (proverbss) that can be used as a source of character education. This research belongs to the category of descriptive qualitative research. The results showed that there were 9 (nine) character values contained in the Simalungun limbaga (proverbs) namely: religious, hard working, honest, disciplined, independent, rewarding achievement, responsibility, social care, and peace-loving.